From chaos through cosmos toward coinonia - Praper, Peter (Psihološka obzorja (Ljubljana), 2008)
The phenomenon of group cohesion is among most examined in group psychotherapy and repeatedly confirmed as the one of the most important curative factors. It is defined as a force of a symbiotic unity. On the other hand, the phenomenon of coherence is mainly understood as a harmonic connection of different members. Both phenomena, observed through sequences of the time in a groupanalytic group, appeared as the result of the developmental processes of individuals in the group and of the group as a whole. The observation brought to a hypothesis that we are facing the parallelism of the individuation processes and group developmental process that have involved both - group-analytic and everyday interpersonal life. Group cohesion appeared as the result of the overcome chaotic paranoid position. The group, previously experienced as unknown and intimidating, becomes a symbiotic object, safe place gradually supporting the improving autonomy of individual members, mainly through important everyday relationships. Simultaneously and gradually group-analytic culture is changing from chaos and autism to equality, cohesion in the sense of "one mind", toward coherence of interesting different members, from "forming and norming" to "performing". It seems that group cohesion and group coherence are not phenomena per se but rather two positions in a group-developmental line, going from autism through cohesion and differentiation towards coherent interactive relationships.
Keywords: skupinska psihoterapija; skupinska kohezija; koherenca; skupinski procesi